Audit Quality of The Engagement Partner and Audit Firm - Sambuaga, Elfina Astrella; Herusetya, Antonius (Universitas Muhammadiyah Surakarta, 2022)
This study examines the effect of the number of clients and complexity on audit quality at the engagement partner and public accounting firm levels. The discretionary accrual and real activities manipulation models are used to assess the audit quality at the engagement partner and public accounting firm levels. From 2013 to 2018, this study examined 506 firm-year observations for companies in the industrial sector listed on the Indonesian Stock Exchange. Using multiple linear regressions and controlling for year and industry fixed effects, our study discovered that the client complexity handled by engagement partners has an association with the engagement partners’ audit quality declining using discretionary accruals. However, our study discovered no relationship between the number of clients at the engagement partner and audit firm levels, and client complexity at the audit firm level that influences audit quality. Thus, the findings of our study suggest to standard setters, capital market participants, and other stakeholders that audit quality at the engagement partner level remains a significant concern.